Management systems on nitrogen absorption by corn in an Oxisol in the Cerrado - Figueiredo, Cícero Célio de; Resck, Dimas Vital Siqueira; Gomes, Antonio Carlos; Urquiaga, Segundo (Pesquisa Agropecuaria Brasileira, 2005)
The objective of this work was to evaluate the effect of different management systems on nitrogen absorption by corn in an Oxisol in the Cerrado. Total nitrogen (Ntotal), soil and mineral fertilizer derived nitrogen (Ndsolo and Ndfm, respectively), and N-fertilizer recovery efficiency (ERNF) taken by corn were determined. Eight management systems comprised by different implements and crop residues incorporation times were studied. The sampling plan was accomplished by simple random sampling. The soil was the main N source. Under no-till or minimum tillage, corn grains showed greater N content (Ntotal, Ndfm, and Ndsolo), as well as ERNF, than under moldboard plow with crop residues incorporated after harvesting treatment. The disk and moldboard's action plows on soil properties as well as crop residues incorporation time, before planting and after harvesting, did not affect the N content in the corn grains (Ntotal and Ndfm), although they presented differences in the absorption dynamics related to N fertilizer broadcasting periods .